Philosophical Study Of Youth Addictive Attitude Formations In The Virtual World (Zien Journal of Social Sciences and Humanities, 2026)
The article analyzes the positive and negative aspects of the virtual environment, its impact on the spiritual world, psychological state and social relations of young people. Also, the addiction of young people to the Internet and social networks, the causes of phenomena such as "hikikomori", and the factors leading to their isolation from society are examined based on scientific literature and statistical data. The study focuses on the issues of ensuring a balance between real and virtual life through a healthy lifestyle of young people, national values and information security.